Homozygous familial hypercholesterolemia: modern aspects of pathogenesis, diagnostics and treatment - V. К. Zafiraki; Е. D. Kosmacheva; I. N. Zakharova; V. A. Korneva; A. V. Susekov (Медицинский совет, 2018)
Homozygous familial hypercholesterolemia is a rare genetic disease featuring extremely high of low-density lipoprotein blood level, cutaneous and tendon xanthomas and accelerated atherosclerosis with often manifestions in the first 2 decades of life, resulting to premature death due to atherosclerosis-related diseases. Modern combined lipid-lowering therapy is able to increase life duration considerably for these patients.